Learners’ Perceptions of Language Remote Teaching during the COVID-19 Pandemic - Omar Colombo; Tamara Boscia (Universitas Muhammadiyah Yogyakarta, 2022)
This paper investigated the learners’ perception and satisfaction of a distance learning course conducted by the French and Italian lecturers as foreign languages in a Malaysian university, during the first wave of the COVID-19 pandemic, from April to July 2020. The study aims to improve online and blended learning and teaching since distance learning is still being implemented because of the pandemic. A distance course perception and satisfaction survey were administered to collect the data. Descriptive statistics of the learners’ scores (based on a five-point Likert scale) highlighted that students appreciated the course structure/design and the learner-teacher and learner-learner interactions, while the general level of satisfaction for the online course as a whole remained moderate. It also underlined the negative influence of emergency remote teaching (ERT) on the learners’ psychology, affecting students’ perceptions and task value. The French and Italian lecturers acknowledged the results of this paper and made the necessary changes to enhance the quality of distance teaching, especially by improving the interpersonal online interactions and encouraging students to become independent learners.